Model of Internalization of Religious Moderation Values in Salafiyah Boarding Schools - Rohmadi Rohmadi; Duski Ibrahim; Munir Munir (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2024)
This study aims to analyze the process of internalizing religious moderation values at the Salafiyah Islamic Boarding School, Rubath Al Muhibbien, Palembang. Religious moderation is crucial for maintaining stability and avoiding excessive religious interpretations that may violate humanitarian values, social agreements, and public order. Salafiyah Islamic boarding schools were chosen as the focus due to their pivotal role in fostering a moderate understanding of Islam, particularly in instilling these values in their students. The research utilized a qualitative phenomenological approach. Key informants included school leaders, administrators, teachers, students, alumni, and the general community. Activities observed encompassed the internalization process of religious moderation values, with classical Islamic texts (kitab kuning) serving as supporting documents: data collection methods involved observations, in-depth interviews, and written and oral documentation. The Miles and Huberman data analysis method, known for its three primary activities, data reduction, data display, and conclusion drawing or verification was employed. The findings reveal a model of internalizing religious moderation values at the Salafiyah Islamic Boarding School, consisting of three stages: value transformation, transaction, and internalization. The first stage involves value transformation through conceptual, institutional, operational, and architectural dimensions. The second stage consists of implementing advisory strategies and customary practices to instil values among students. The third stage incorporates role modelling, habituation, exemplification, advisory roles, promises, threats, and disciplinary measures. By focusing on one Islamic boarding school, the research results may not fully reflect the internalizing religious moderation values ​​in other Islamic boarding schools with different characteristics, cultures, and teaching methods. The originality lies in the model of internalizing religious moderation values ​​that have been developed. This holistic approach combines unique conceptual, institutional, operational, and architectural aspects and strategies relevant to the culture and traditions of Islamic boarding school education.